Production of Biodiesel from Waste Cooking Oil using Calcium Oxide Nanocatalyst (Journal of Science and Technology Research, 2026)
The production of biodiesel from waste cooking oil (WCO) represents a sustainable  and environmentally friendly approach to waste management and renewable energy  generation. This study explores the use of calcium oxide (CaO) nanocatalyst in the  transesterification process of converting WCO into biodiesel. CaO nanocatalyst is  favored for its high catalytic activity, low cost, and environmental compatibility. In  this study, calcium oxide (CaO)-based nano-catalyst was prepared through calcination  process using local waste eggshells to produce biodiesel. The nano-CaO catalysis impact  was investigated in a two-step transesterification chemical reaction from waste cooking  oil (WCO) to biodiesel. Transmission electron microscope (TEM), Fourier transform  infrared (FT-IR) spectroscopy and X-ray diffraction (XRD) techniques were utilized  to confirm the CaO nano-catalyst. It was discovered that the CaO catalyst made from  eggshell waste was an efficient, stable, and reasonably priced heterogeneous catalyst to  be highly effective for the manufacture of biodiesel. The production of biodiesel was  confirmed through FTIR analysis. Moreover, the biodiesel properties such as calorific  value, specific gravity, acid value, density, flash point, kinematic viscosity, ash content,  water content and cetane number were investigated and found to be similar with the  EN 14214 biodiesel standard. It is expected that producing biodiesel using eggshell as  a heterogeneous catalyst offers an economical and sustainable method of producing  green fuel. This study underscores the potential of CaO nanocatalyst in enhancing  the efficiency and sustainability of biodiesel production, offering a viable solution for  waste management and energy production. J. of Sci. and Tech. Res. 6(2): 33-41, 2025